2007
DOI: 10.1016/j.pharmthera.2006.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Manganese neurotoxicity: A focus on the neonate

Abstract: Manganese (Mn) is an essential trace metal found in all tissues, and it is required for normal amino acid, lipid, protein, and carbohydrate metabolism. While Mn deficiency is extremely rare in humans, toxicity due to overexposure of Mn is more prevalent. The brain appears to be especially vulnerable. Mn neurotoxicity is most commonly associated with occupational exposure to aerosols or dusts that contain extremely high levels (> 1-5 mg Mn/m 3 ) of Mn, consumption of contaminated well water, or parenteral nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
141
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 224 publications
(148 citation statements)
references
References 141 publications
3
141
0
4
Order By: Relevance
“…Excitotoxic neuronal injury induced by elevated glutamate levels is considered one of the main mechanisms of Mn-induced neurotoxicity (34,35). Our findings provide substantial evidence that YY1 is a mediator of Mn-induced repression of EAAT2.…”
Section: Discussionsupporting
confidence: 58%
“…Excitotoxic neuronal injury induced by elevated glutamate levels is considered one of the main mechanisms of Mn-induced neurotoxicity (34,35). Our findings provide substantial evidence that YY1 is a mediator of Mn-induced repression of EAAT2.…”
Section: Discussionsupporting
confidence: 58%
“…The most obvious explanation is that these changes in presynaptic functioning are caused by Mn-induced neurotoxicity affecting dopamine terminals. General support for this explanation is provided by a large number of in vivo and in vitro studies showing that Mn is toxic to dopamine-containing cells of the basal ganglia (for reviews, see Hirata, 2002;Takeda, 2003;Erikson et al, 2007). Other classes of neurons (e.g., glutamatergic and GABAergic) in the basal ganglia also exhibit a neurotoxic response to Mn (Fitsanakis et al, 2006b), therefore loss of neuronal inputs might be secondarily responsible for some of the perturbations in presynaptic dopamine functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with reports of previous researchers, we found that the affected infants were more immature Early amino-acid support and cholestasis M Steinbach et al and had lower birth weight than the non-affected group. 5,[7][8][9] Other investigations have also described an association between cholestasis and the quantity and formulation of amino acids administered parenterally, excess caloric intake of fats and carbohydrates, 10,11 toxicity of trace minerals, [12][13][14][15][16] male gender, 17 perinatal asphyxia, 18 phototoxicity of multivitamin 2 Aggressive administration of parenteral amino acids to improve protein accretion rates in very preterm neonates has been supported in the literature. [24][25][26][27] Although tolerance of high-dose amino acids has been described, researchers acknowledge that sensitive tests to monitor amino-acid toxicity are not readily available in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%